Recent Advances of CRISPR/Cas9-Based Genetic Engineering and Transcriptional Regulation in Industrial Biology - Zhang, Shangjie; Guo, Feng; Yan, Wei; Dai, Zhongxue; Dong, Weiliang; Zhou, Jie; Zhang, Wenming; Xin, Fengxue; Jiang, Min (Frontiers in Bioengineering and Biotechnology, 2020)
Industrial biology technology plays a crucial role in the fields of medicine, health, food, energy and so on. However, the lack of efficient genetic engineering tools has restricted the rapid development of industrial biology. Recently, the emergence of clustered regularly interspaced short palindromic repeats-CRISPR associated protein 9 (CRISPR-Cas9) system has brought a breakthrough in the genome editing technologies due to its high orthogonality, versatility and efficiency. In this review, the advances of industrial biology employed CRISPR-Cas9 system were summered and compared in terms of its application in bacteria, yeast and filamentous fungi. Furthermore, the cooperation between CRISPR-Cas9 with synthetic biology was discussed to help build complex and programmable gene circuits, which can be used in industrial engineering applications.